An excess Gibbs free energy based model to calculate viscosity of multicomponent liquid mixtures. (November 2015) - Pinto, Diego D.D.; Svendsen, Hallvard F.
Abstract : Highlights: We propose a correlation to calculate the viscosity of multicomponent mixtures. The model uses an analogy to excess Gibbs energy (GE) models. In this work, we chose the functional form of the NRTL model to represent the GE. The resulting model is called NRTL-DVIS and it requires few adjustable parameters. The model represented the tested systems with good accuracy. Abstract: Solution densities and viscosities are important parameters for the design and simulation of absorption processes. Accurate models are needed and in this work, a new model for calculating the liquid viscosity of mixtures is presented. The model uses an analogy to excess Gibbs energy models to account for the deviation from a simple mixing rule based on the pure component viscosities. In this work, we chose the functional form of the NRTL model to represent the excess Gibbs energy and the resulting model is referred to as NRTL-DVIS. Eleven systems (eight binaries and three ternary) were chosen for testing the accuracy of the model. The ternary systems were built from the optimized binaries and pure component systems. With few adjustable parameters, the NRTL-DVIS model represented the tested systems with good accuracy. With few exceptions the calculated total deviation (AARD) was within 3.5%. The NRTL-DVIS model shows better accuracy than other models proposed in the literature.